Makna Filosofis dan Saintifik Terkait Keislaman - Royani, Ahmad; Arinalhaq, Muhammad Syauqi; Rahman, Akmal Fadilah; Rosa, Andi; Muhsin, Masrukhin (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2024)
This study explores the philosophical and scientific meanings related to Islam. Philosophy and scientification in the Islamic context are complementary in understanding reality and enhancing human knowledge. Through the integration of faith and reason, Islamic tradition has successfully developed a knowledge system grounded in moral and spiritual principles. Consequently, scientification in Islam is not merely the practical application of technology but also an effort to comprehend God's creation and elevate human dignity holistically. Ontology in the Islamic context refers to an in-depth investigation into the nature of existence and reality as they relate to Islamic teachings. Several principles of Islamic epistemology pertain to the definition of knowledge, its sources, objects, and scientific methods within Islamic epistemology. In Islam, axiology examines values or ethics, where ethics (akhlaq) serves as the ultimate goal for those pursuing knowledge itself.